Effects of a Postbiotic Saccharomyces and Lactobacillus Ferment Complex on the Scalp Microbiome of Chinese Women with Sensitive Scalp Syndrome - Wang Y; Li J; Wu J; Gu S; Hu H; Cai R; Wang M; Zou Y (Dove Medical Press, 2023)
Yue Wang,1,2 Jun Li,3 Jianming Wu,3 Shihong Gu,3 Huishu Hu,3 Rongjuan Cai,2 Man Wang,4 Yue Zou3 1Institute of Shanghai Oriental Beauty Valley, Shanghai Institute of Technology, Shanghai, People's Republic of China; 2School of Perfume and Aroma Technology, Shanghai Institute of Technology, Shanghai, People's Republic of China; 3R&D Center, JALA (Group) Co., Ltd, Shanghai, People's Republic of China; 4Department of Nutrition, Shanghai Jiao Tong University Affiliated Sixth People's Hospital South Campus, Shanghai, People's Republic of ChinaCorrespondence: Yue Zou, R&D Center, JALA (Group) Co., Ltd, Building 2, No. 333, Guiping Road, Xuhui District, Shanghai, 200233, People's Republic of China, Email zouyue3@jala.com.cnIntroduction: Sensitive scalp is one of the most frequent complaints related to sensitive skin syndrome, characterized by unpleasant sensory reactions in the absence of visible signs of inflammation. In this study, the effects of topical application of postbiotic Himalaya-derived Saccharomyces and Lactobacillus ferment complex (SLFC) on the bacterial and fungal scalp microbiome at the taxonomic level and alleviation of sensitive skin syndrome were investigated.Methods: Firstly, healthy female participants (aged 30- 45) were classified into a healthy scalp group and a sensitive scalp group based on the questionnaire. Thereafter, topical application of SLFC on sensitive scalp as well as scalp microbiome was evaluated, with the difference in the distribution of microbial taxa between healthy and sensitive scalp communities was assessed using 16S rRNA and ITS1 sequencing analysis. In addition, the effect of SLFC on scalp microbiome at the species level for Cutibacterium acnes, Staphylococcus epidermidis, and Malassezia restricta was evaluated by the qPCR assessment.Results: After treatment with SLFC for 28 days, the abundance of Staphylococcus, Lawsonella, and Fusarium in the sensitive scalp group was highly significantly increased (p < 0.001), while the abundance of Cutibacterium and Malassezia was highly significantly decreased (p < 0.001). Furthermore, the self-assessment questionnaire indicated a syndrome alleviation effect of 100% after 28 days with a twice-daily application of the SLFC.Discussion: The obtained results would help to better understand the microbial community of the sensitive scalp and provide useful information on utilization of SLFC for maintaining a healthy scalp and modulating the scalp microbiome.Keywords: sensitive scalp, scalp microbiome, postbiotics, microbial diversity, questionnaire analysis